Impact of urbanization on perceived labor cost changes in manufacturing industries in Hebei of China - Chen, Lisha, 1986-, author 577181; Amran Md. Rasli, supervisor 638741; Fakulti Pengurusan 538641 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Thesis (Doktor Falsafah (Pengurusan))